Heavy Elements and related new phenomena - Greiner, Walter (World Scientific, 1999)
This book reviews recent developments in the field of superheavy elements and the related phenomena of fission, cluster radioactivity, and drip line physics. Both the experimental and theoretical aspects are dealt with in detail. For the production of new elements in the laboratory, the process of cold compound nucleus formation is found to be most favorable both theoretically and experimentally. However, experimentally, hot fusion of nuclei has also been used. Both the physical and chemical methods of synthesizing new elements are discussed. The theoretical approaches considered here are those of the quantum-mechanical fragmentation theory, the self-consistent Hartree–Fock theory, and the relativistic mean field theory. Fission, a process inverse to the fusion of two nuclei, is also observed to be most favourably a cold phenomenon. Other important results are bi-modal fission and high n-multiplicity fission, which leads to the hyperdeformed scission mode. Cluster radioactivity is discussed both as a heavy cluster emission process and as super-asymmetric fission. The theory as well as the present experimental status are reviewed. Physics at drip lines is interesting not only for their structural properties but also for their use in the fusion of two nuclei; both aspects are discussed